Preparation of Low Friction MoSex/nc-Mo Coatings Containing Spherical Mo Nanoparticles - Grigoriev, S.; Romanov, R.; Volosova, M.; Matsnev, N.; Fominski, V. (Journal of Coating Science and Technology, 2016)
The possibility of preparation of nanocomposite coatings consisting of a solid lubricant matrix (MoSex) and nanocrystalline metal particles (nc-Mo) was demonstrated using pulsed laser deposition from synthesized target MoSe2.The particles had spherical shapes and their sizes were about 5 - 50 nm. The content of the nc-Mo nanoparticles in the MoSex/nc-Mo coatings was varied by changing the laser irradiation regimes and the conditions of expansion of the laser plume from the target to substrate. It was established that the tribological properties of the nanocomposite coatings MoSex/nc-Mo are depended on the concentration of nanoparticles in the bulk of the coatings as well as on the structure of the coating matrix. The MoSex/nc-Mo coating with increased crystalline order of matrix obtained on a steel substrate reduced the friction coefficient to ~0.04 during steel ball sliding in air of laboratory humidity. Probable mechanisms of nanoparticle formation were proposed and a role of these particles in the wear of the nanocomposite MoSex/nc-Mo coatings was discussed.